Microwave-assisted rapid synthesis of bismuth molybdate with enhanced oxidative desulfurization activity. (1st January 2023) - Zhang, Zhanjun; Zeng, Xingye; Wen, Liyuan; Liao, Siying; Wu, Shikui; Zeng, Ying; Zhou, Rujin; Shan, Shufeng
Highlights: The morphology and structure of the synthesized catalysts can be modified by adjusting the pH under microwave-assisted. The bismuth molybdate prepared pH 1 exhibits excellent oxidative desulfurization of DBT and 4, 6-DMDBT. The stability of bismuth molybdate composite was investigated by cyclic ODS experiments. Abstract: In this work, six different bismuth molybdate catalysts were synthesized by a fast microwave-assisted hydrothermal method. By adjusting the pH in the preparation process, the morphology and structure of the synthesized catalysts can be modified, and the transition of Bi2 MoO6 crystals to Bi3.2 Mo0.8 O7.5 crystals can be selectively achieved. The sample prepared at pH 1, BMO-1, exhibited excellent activity for oxidizing sulfur compounds in fuel oil at 60 °C with a molar hydrogen peroxide to sulfur ratio of four, achieving removal rates of dibenzothiophene, 4, 6-dimethyldibenzothiophene, and benzothiophene of 99.71%, 99.68%, and 77.95%, respectively. When recycling the catalyst seven times, the removal rate of dibenzothiophene still reached 98.07%. A probable mechanism for the oxidative desulfurization process was proposed. This work not only offers a high-efficiency, method for the rapid preparation of bismuth molybdate catalysts but also extends the application of this catalyst in the field of deep oxidative desulfurization.